2002
DOI: 10.1074/jbc.m208138200
|View full text |Cite
|
Sign up to set email alerts
|

Fyn and p38 Signaling Are Both Required for Maximal Hypertonic Activation of the Osmotic Response Element-binding Protein/Tonicity-responsive Enhancer-binding Protein (OREBP/TonEBP)

Abstract: When cells are challenged by hyperosmotic stress, one of the crucial adaptive responses is the expression of osmoprotective genes that are responsible for raising the intracellular level of compatible osmolytes such as sorbitol, betaine, and myo-inositol. This is achieved by the activation of the transcription factor called OREBP (also known as TonEBP or NFAT5) that specifically binds to the osmotic response element (ORE) or tonicity-responsive enhancer that enhances the transcription of these genes. Here we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 36 publications
6
130
1
Order By: Relevance
“…Hyperosmotic stress enhances translocation of NFAT5 into the nucleus through phosphorylation by signal molecules, such as ATM, Fyn, p38, and protein kinase A (32)(33)(34). In this study, we demonstrated, for the first time, that NFAT5 activity was regulated through the proteasome-mediated proteolysis pathway under cytotoxic conditions, proposing a novel regulatory mechanism of NFAT5 activity.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Hyperosmotic stress enhances translocation of NFAT5 into the nucleus through phosphorylation by signal molecules, such as ATM, Fyn, p38, and protein kinase A (32)(33)(34). In this study, we demonstrated, for the first time, that NFAT5 activity was regulated through the proteasome-mediated proteolysis pathway under cytotoxic conditions, proposing a novel regulatory mechanism of NFAT5 activity.…”
Section: Discussionmentioning
confidence: 69%
“…Taken together, it is likely that Dox-induced degradation of NFAT5 is mediated by a proteasome-mediated proteolytic process in an ubiquitinindependent manner. NFAT5 activity is regulated by some protein kinases (32)(33)(34). NFAT5 is phosphorylated under hypertonic condition, and NFAT5 phosphorylation is shown to be a critical event for nuclear translocation, followed by DNA binding (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 10, p38MAPK and MEK-ERK inhibitors, but not the JNK inhibitor, blocked the nuclear translocation of TonEBP/OREBP/NFAT5 induced by NaCl or mannitol, suggesting that p38MAPK and MEK-ERK signaling pathways (44,45) are associated with the nuclear distribution of TonEBP/ OREBP/NFAT5 mediated by hypertonicity. This result is also consistent with the effects of MAPK inhibitors on MCP1 mRNA and protein levels, as shown in Figs.…”
Section: Probementioning
confidence: 94%
“…These include PKAc (11), p38 (9, 10), and Fyn (10). Like ATM, each of them is necessary for full activation of TonEBP͞OREBP transcriptional activity by high NaCl, but inhibition of any of them, singly, does not fully prevent the activation.…”
Section: Convergence Of Multiple Pathways Is Necessary For High Nacl Tomentioning
confidence: 99%
“…There is evidence that several protein kinases participate in activation of TonEBP͞OREBP by hypertonicity, including p38 (9, 10), Fyn (10), and protein kinase A (PKAc) (11). However, there might be additional ones.…”
mentioning
confidence: 99%